Improving Students’ Speaking Skill by Using the Cooperative Learning Method through Think Pair Share (TPS) at SMK Negeri 4 Halmahera Tengah - S Syamsia; Ardila Sidik (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2019)
This research is conducted to find out the students’ speaking skills by using the cooperative learning method through think pair share (TPS). Based on the observation and interview conducted by the researcher to SMK NEGERI 4 Halmahera Tengah, some problems were still found in the students’ abilities in English, especially in speaking. The students’ speaking skills were relatively low. They had difficulties in expressing ideas opinions orally as they were afraid of making mistakes and not confident to speak English. They still had difficulties in pronouncing certain English words. To be able to speak, instead of pronunciation, the richness of vocabulary was also important. In this research, the researcher uses classroom action research ( CAR ). The Setting was SMK N 4 Halmahera Tengah and the subjects were all students of class XI of SMK N 4 Halmahera Tengah in the academic year 2018/ 2019 with a total of 20 students. Based on the results of the students' speaking skills in the first cycle showed that out of 20 students of class XI SMK N 4 Halmahera Tengah. just 7 students were passed KKM while 13 students were not passed KKM. So in the first cycle was unsuccessful and the researcher has to continue for the next cycle. The result of the second cycle showed that 15 of 20 students of SMK N 4 Halmahera Tengah class XI are able to pass the KKM or in other words, they can achieve their speaking in the second cycle, while 5 were not achieved the KKM value ( ≥ 75 ). It can be concluded that the cooperative learning process through think pair share ( TPS ) can improve students’ speaking skills at SMK N 4 Halmahera Tengah.